Social Engagement, Cognition, Depression and Co-morbidity in Sensory Impaired Nursing Home Residents - Petrovsky, Darina V. (Res Gerontol Nurs, 2019)
Sensory impairment specifically, vision and hearing impairment, among nursing home (NH) residents decreases their ability to socially engage. It is not known, however, to what extent visual, hearing or dual impairment is associated with social engagement. The aims of this retrospective, cross-sectional descriptive study were to determine the relationship between social engagement and a) levels of sensory impairment (vision, hearing and dual); b) depression; and c) cognition. We analyzed baseline data from 213 sensory impaired NH residents from the I-SEE study. Multivariable model results demonstrated that sensory impairment was not associated with social engagement when adjusting for all covariates. Less depression, better cognition and greater co-morbidity were significantly associated with greater social engagement. Clinicians should be aware of these risks to social engagement in sensory impaired NH residents and monitor for decreased social engagement and isolation in residents with less comorbidities, higher depression levels and poorer cognition.